Morfologi dan Biometri Spermatozoa Anoa (Bubalus Sp.) yang Diwarnai dengan Pewarna William’s dan Eosin-Nigrosin - Yudi Yudi; T L Yusuf; B Purwantara; M Agil; T Wresdiyati; D Sayuthi; Aditya Aditya; J Manansang; R Sudarwati; Y T Hastuti (Media Peternakan, 2010)
Anoa is Indonesia endemic fauna that included into Appendix I by CITES. Anoa breeding efforts have not succeed, due to their agressivity, soliter, wildness and monogamous. The aim of this experiment was to observe morphology and biometry of anoa's sperm stained using William's (W) and eosin-nigrosin (EN). Semen was collected from two male anoas by electroejaculator. Slides was made for morphology and biometry observation of ejaculate. The results showed that abnormal sperm morphology of the mature anoa (10 years) was 32.27%-35.00%, meanwhile the young one (3 years) was 24.03%-31.89%. In mature anoa, measurement for head width, and midpiece and tail length of sperm were not signficantly different between W and EN staining, but significantly different (P < 0.05) for head and total length. In the young anoa, sperm biometry for head width was not significanly different between W and EN staining. In both W and EN staining, biometry for head width and total length were not significantly different between mature and young anoas, but significantly different for head, midpiece and tail length. According to sperm morphology, semen from the young anoa was slightly better than those of the mature anoa. Staining method and age could affect to biometry of the anoa's sperm.